All‐Printed, Stretchable Zn‐Ag2O Rechargeable Battery via Hyperelastic Binder for Self‐Powering Wearable Electronics. Issue 8 (19th December 2016) - Kumar, Rajan; Shin, Jaewook; Yin, Lu; You, Jung‐Min; Meng, Ying Shirley; Wang, Joseph
Abstract : While several stretchable batteries utilizing either deterministic or random composite architectures have been described, none have been fabricated using inexpensive printing technologies. In this study, the authors printed a highly stretchable, zinc‐silver oxide (Zn‐Ag2 O) battery by incorporating polystyrene‐ block ‐polyisoprene‐ block ‐polystyrene (SIS) as a hyperelastic binder for custom‐made printable inks. The remarkable mechanical properties of the SIS binder lead to an all‐printed, stretchable Zn‐Ag2 O rechargeable battery with a ≈2.5 mA h cm −2 reversible capacity density even after multiple iterations of 100% stretching. This battery offers the highest reversible capacity and discharge current density for intrinsically stretchable batteries reported to date. The electrochemical and mechanical properties are characterized under different strain conditions. The new stress‐enduring printable inks pave ways for further developing stretchable electronics for the wide range of wearable applications. Abstract : Printable, stretchable, rechargeable zinc batteries based on a hyperelastic binder on textile provide an inexpensive and durable powering source for wearable electronics. The stretchable battery demonstrates a reversible capacity density of ≈2.5 mA h cm −2 even after multiple iterations of deformation (100% strain).